PENGARUH VARIASI SUHU PEMADATAN CAMPURAN TERHADAP KINERJA COLD PAVING HOT MIX ASBUTON (CPHMA) DENGAN PENAMBAHAN SEMEN PORTLAND: The Effect of Compaction Temperature Variations on the Performance of Cold Paving Hot Mix Asbuton (CPHMA) With The Addition of Portland Cement - Salsabila, Fera Fitri; Hasyim, Hasyim; Azizzah, Fatimah Nurul (Ganec Swara, 2026)
Indonesia has significant potential for natural asphalt derived from Buton Island, Southeast Sulawesi, known as Asbuton. One product developed from its utilization is Cold Paving Hot Mix Asbuton (CPHMA), which can serve as a road surface layer and offers the advantage of low-temperature compaction. However, the performance of CPHMA mixtures is strongly influenced by compaction temperature and the use of additives. Therefore, this study aimed to determine the effect of variations in compaction temperature and the addition of Portland cement on the volumetric and mechanical characteristics of CPHMA mixtures. The research was conducted at the Highway Laboratory, Civil Engineering Study Program, Mataram University. Variations included compaction temperatures of 30°C, 90°C, and 150°C, and Portland cement contents of 0%, 7%, 8%, and 9%. Tests performed consisted of sieve analysis, aggregate density, aggregate impact value, and evaluation of volumetric (VMA, VIM, VFB) and mechanical characteristics using the Marshall method. The results indicated that compaction temperature significantly affected mixture performance, where higher temperatures produced denser and more stable mixtures. The addition of Portland cement also enhanced bond strength. The optimum condition was achieved at 150°C with 8% cement content, providing the best balance between volumetric properties and mechanical performance.